The Decadence of Aesthetics and the Aesthetics of Decadence: Portraits of the Artist from Baudelaire to Des Esseintes. (November 2014) - Amy, Leggette
<x content-type="archive" xml:space="preserve">Abstract</x> The temptation of decadence persists in the critical tendency to diagnose authors and their works, to trace out genealogies of an infamous familial line, from Charles Baudelaire to Joris-Karl Huysmans. This study proposes an alternative approach to defining decadence by its descent, assembling a discursive inheritance of portraits of the artist: descriptions of the artist-as-subject that serve as critical representations of aesthetic ideas. By examining how portraits of the artist function in Baudelaire's art criticism, in the formulations of his posthumous critics, and in Huysmans's compendious novel, I will trace out an unacknowledged continuity from the decadence of aesthetics to the aesthetics of decadence. Decadence, as it descends from Baudelaire through portraits of the artist, originates in the problem of subjectivity in aesthetics.